The relationship between dental health knowledge and practices of mothers seeking treatment in UPCD - Montano, Viviane E.; Ong, Blythe Jayne C.; Sembrano, Marilou H. (Adviser).
An individual's knowledge and practice are interrelated with each other. These are further affected by several factors. The aim of this study was to describe the relationship between the dental health knowledge and dental health practice of mothers seeking treatment in UPCD, its relation to the mothers' profile, i.e. age, occupation, number of children, educational attainment, economic status and marital status; to find out whether or not these mothers have sufficient dental health knowledge, and whether or not they translate these knowledge into practice. Convenience sampling was utilized. A descriptive analysis was done on the scores of the respondents using the McNemar test, test for homogeneity, Chi-square test, and Pearson correlation coefficient. The distribution on the basis of each variable showed that majority of the respondents had sufficient dental health knowledge, and exhibited good dental health practice. There is a positive relationship between the dental health knowledge and dental health practice of mothers seeking treatment in UPCD.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Health knowledge, Attitudes, Practice; Mothers -- Dental care; Children -- Dental care